All‐Solid‐State Lithium‐Sulfur Batteries Using Sulfurized Alcohol Composite Material with Improved Coulomb Efficiency. Issue 12 (30th July 2019) - Takeuchi, Tomonari; Kojima, Toshikatsu; Kageyama, Hiroyuki; Kobayashi, Hironori; Mitsuhara, Kei; Nakanishi, Koji; Ohta, Toshiaki
Abstract : Sulfurized alcohol composite (SAC), a new type of organosulfur material, is applied to an all‐solid‐state cell with a sulfur‐based solid electrolyte (SE), Li3 PS4 . The cell shows high specific capacity (600–800 mAh g −1 ), and the initial coulomb efficiency is improved by mechanically milling the cathode layer (SAC + SE). The improvement is attributed to the partial lithiation of the SAC sample by milling with SE, which is confirmed by S K‐edge X‐ray absorption fine structure measurements. Such prelithiation is advantageous for fabricating high‐energy‐density all‐solid‐state cells. Abstract : A new type of organosulfur material, sulfurized alcohol composite (SAC), is applied to an all‐solid‐state cell. The cell shows high specific capacity (600–800 mAh g −1 ) and improved initial coulomb efficiency by milling SAC and solid electrolyte. The improvement is attributed to the partial lithiation of the SAC sample and is advantageous for fabricating high‐energy‐density all‐solid‐state cells.